2013
DOI: 10.1007/s10633-013-9401-2
|View full text |Cite
|
Sign up to set email alerts
|

Pattern electroretinogram in neuromyelitis optica and multiple sclerosis with or without optic neuritis and its correlation with FD-OCT and perimetry

Abstract: Pattern electroretinogram measurements were able to detect RNFL loss in MS + ON and NMO eyes, with a performance comparable to OCT. PERG amplitude measurements were reasonably well correlated with OCT-measured parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
4
19
0
4
Order By: Relevance
“…Indeed, many studies have reported a reduction in macular volume and macular ganglion cell complex thickness in MS [8,19,20,23]. Similarly, in the present study, GC-IPL and mNFL thicknesses were lower in MS patient's eyes than in HC eyes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Indeed, many studies have reported a reduction in macular volume and macular ganglion cell complex thickness in MS [8,19,20,23]. Similarly, in the present study, GC-IPL and mNFL thicknesses were lower in MS patient's eyes than in HC eyes.…”
Section: Discussionsupporting
confidence: 81%
“…The association between RNFL thinning and MS is marked by various studies [3][4][5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Likewise, in this study, MS patients' eyes showed statistically significantly lower values of the total RNFL than the HC eyes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…48 Visual field sensitivity (as measured by the mean deviation (MD) from age-matched normal values) is reduced in MS patients relative to normal subjects, with the greatest reduction being observed in those eyes with a history of ON. 49,50 Mean deviation is correlated with TD-OCT-derived RNFL thickness in MS eyes with a history of ON, 51,52 although the quantitative relationship with deeper retinal layers remains unstudied. Given that MS patients are prone to fatigue 53 and the adverse effects of fatigue on both visual sensitivity and reliability when performing perimetry, 48 more objective measures of visual function (such as electrophysiology) are likely to be helpful when assessing MS patients.…”
Section: Relationship Of Oct Parameters With Clinical Outcome Measuresmentioning
confidence: 99%
“…Nos últimos anos, novos aparelhos de TCO foram introduzidos possibilitando incorporar softwares para este tipo de análise o que melhorou em muito o desempenho dos parâmetros maculares na quantificação da integridade neural da retina em várias afecções da via visual anterior incluindo o glaucoma (74)(75)(76) .…”
Section: Avaliação Funcional E Estruturalunclassified